2007
DOI: 10.1007/s10856-006-0700-y
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of an injectable Macroporous Calcium Phosphate Cement

Abstract: Although Calcium Phosphate Cements (CPC) are highly biocompatible and osteconductive materials, its resorption rate still remains too slow for some applications. In this work the introduction of Macroporosity in an injectable CPC is evaluated as a way to accelerate resorption and to increase bone ingrowth. A Macroporous and a standard CPC were injected just after preparation in a defect drilled in rabbit femur for their in vivo evaluation. The foaming agent used was Albumen, which gave up to a 75% porosity. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 36 publications
8
58
0
2
Order By: Relevance
“…For example, as Biobone ® is more porous than BoneSource TM , the discovered diversity could be due to the differences in porosity [4,5]. The latter conclusion is confirmed by the results of other studies: a positive influence of the porosity on resorption rates was found [311]. The interested readers are referred to a study on the suitability of hardened and porous calcium orthophosphate formulations as scaffolds for bone regeneration, using a rabbit model [418].…”
Section: Bioresorption and Replacement Of The Self-setting Formulatiomentioning
confidence: 61%
See 1 more Smart Citation
“…For example, as Biobone ® is more porous than BoneSource TM , the discovered diversity could be due to the differences in porosity [4,5]. The latter conclusion is confirmed by the results of other studies: a positive influence of the porosity on resorption rates was found [311]. The interested readers are referred to a study on the suitability of hardened and porous calcium orthophosphate formulations as scaffolds for bone regeneration, using a rabbit model [418].…”
Section: Bioresorption and Replacement Of The Self-setting Formulatiomentioning
confidence: 61%
“…For example, an appropriate cohesion was achieved when no disintegration of the paste was observed in the fluid [153,308]. This can be accomplished by keeping a high viscosity for self-setting pastes [22] or using cohesion promoters (e.g., 1% aqueous solution of sodium alginate [200,310,311], as well as other chemicals [200,[312][313][314] (Table 3) are not injectable and blood must be kept away from the implanting site until setting [4,5]. A poor cohesion has been associated to a poor biocompatibility that might lead to inflammatory reactions [309].…”
Section: Rheological Propertiesmentioning
confidence: 99%
“…9), which still offered satisfactory strength for bone cement application. Although the porous structure of set CO 3Ap cement obtained in this study might not enhance the mechanical property, it would increase resorbability and improve cell attachment 28) . In vivo experiments using the CO3Ap cement developed in this study have commenced.…”
Section: Discussionmentioning
confidence: 78%
“…Micropores (<10µm) can be sufficient for circulation of body fluids but macroporosity (>100µm) is needed for cell colonization [47].…”
Section: Porositymentioning
confidence: 99%